Functionally graded material of 304L stainless steel and inconel 625 fabricated by directed energy deposition: Characterization and thermodynamic modeling. (15th April 2016) - Carroll, Beth E.; Otis, Richard A.; Borgonia, John Paul; Suh, Jong-ook; Dillon, R. Peter; Shapiro, Andrew A.; Hofmann, Douglas C.; Liu, Zi-Kui; Beese, Allison M.
Abstract: Many engineering applications, particularly in extreme environments, require components with properties that vary with location in the part. Functionally graded materials (FGMs), which possess gradients in properties such as hardness or density, are a potential solution to address these requirements. The laser-based additive manufacturing process of directed energy deposition (DED) can be used to fabricate metallic parts with a gradient in composition by adjusting the volume fraction of metallic powders delivered to the melt pool as a function of position. As this is a fusion process, secondary phases may develop in the gradient zone during solidification that can result in undesirable properties in the part. This work describes experimental and thermodynamic studies of a component built from 304L stainless steel incrementally graded to Inconel 625. The microstructure, chemistry, phase composition, and microhardness as a function of position were characterized by microscopy, energy dispersive spectroscopy, X-ray diffraction, and microindentation. Particles of secondary phases were found in small amounts within cracks in the gradient zone. These were ascertained to consist of transition metal carbides by experimental results and thermodynamic calculations. The study provides a combined experimental and thermodynamic computational modeling approach toward the fabrication and evaluation of a functionally graded material made by DED additive manufacturing. Graphical abstract: